2022
DOI: 10.1002/tea.21803
|View full text |Cite
|
Sign up to set email alerts
|

Distributing epistemic functions and tasks—A framework for augmenting human analytic power with machine learning in science education research

Abstract: Machine learning (ML) has become commonplace in educational research and science education research, especially to support assessment efforts. Such applications of machine learning have shown their promise in replicating and scaling human‐driven codes of students' work. Despite this promise, we and other scholars argue that machine learning has not yet achieved its transformational potential. We argue that this is because our field is currently lacking frameworks for supporting creative, principled, and critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 52 publications
1
4
0
2
Order By: Relevance
“…The identified advancements and shortcomings of our analysis are in alignment with other reviews and perspectives (Zhai et al, 2020a(Zhai et al, , 2020cKubsch et al, 2023). In their dimension construct, Zhai et al (2020a) found that 81% of the reviewed studies tapped complex constructs indicating the great potential of ML in assessing such constructs.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…The identified advancements and shortcomings of our analysis are in alignment with other reviews and perspectives (Zhai et al, 2020a(Zhai et al, , 2020cKubsch et al, 2023). In their dimension construct, Zhai et al (2020a) found that 81% of the reviewed studies tapped complex constructs indicating the great potential of ML in assessing such constructs.…”
Section: Discussionsupporting
confidence: 69%
“…Along with other researchers (Zhai et al, 2020a(Zhai et al, , 2020cKubsch et al, 2023), we suggest exploring the transformative character of ML in science education beyond automating formative assessment. This includes moving away from perceiving humans as consumers of algorithmic output that takes certain decision-making processes away since such output rarely answers research questions related to the qualitative analysis of cognitive operations (Kubsch et al, 2023). In other words, ML algorithms do not replace human qualitative interpretation; thoughtful human interpretation is more crucial than ever.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Diese ML-Techniken erlauben der Hochschulfachdidaktik, was bislang nur schwer möglich war: Sie bekommt durch die automatisierte Auswertung offener Aufgabenformate datengetriebene Einblicke in die Kompetenzen von Studierenden. 8)…”
Section: Künstliche Intelligenz Und Maschinelles Lernenunclassified